2016
DOI: 10.3329/bjp.v11is1.26844
|View full text |Cite
|
Sign up to set email alerts
|

Determination of eight lignans in Schisandra chinensis and Schisandra sphenanthera

Abstract: A high performance liquid chromatography method for the determination of eight lignans contents in Schisandra chinensis and Schisandra sphenanthera was developed. The chromatographic column was Agilent ZORBAX 300SB-C18 column (4.6 mm × 250 mm?5 ?m). The mobile phase was methanol-water, a gradient elution was conducted and the detection wavelength was at 230 nm. The results showed that the recovery rate of eight lignans was 92.2-102.9% and RSD was 1.5-4.2%. The established content determination method was simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Its main active components are lignans, polysaccharides, and volatile oil. [14][15][16] Some studies have shown that S. chinensis can improve the learning and memory disorders of mice, but these studies lacked a systematic approach, and its mechanism was not studied in sufficient depth. 17 In this study, the models of memory acquisition disorder, memory consolidation disorder, memory reproduction disorder, and aging in mice were established by intraperitoneal injection of scopolamine, chloramphenicol, 40% ethanol, and subcutaneous injection of d-galactose, respectively; the improvement of Schisandra chinensis extract (SCE) on the learning and memory disorders induced by the different agents was observed systematically, and the mechanism explored, which was expected to provide a basis for S. chinensis being used as either a medicine or health food.…”
mentioning
confidence: 99%
“…Its main active components are lignans, polysaccharides, and volatile oil. [14][15][16] Some studies have shown that S. chinensis can improve the learning and memory disorders of mice, but these studies lacked a systematic approach, and its mechanism was not studied in sufficient depth. 17 In this study, the models of memory acquisition disorder, memory consolidation disorder, memory reproduction disorder, and aging in mice were established by intraperitoneal injection of scopolamine, chloramphenicol, 40% ethanol, and subcutaneous injection of d-galactose, respectively; the improvement of Schisandra chinensis extract (SCE) on the learning and memory disorders induced by the different agents was observed systematically, and the mechanism explored, which was expected to provide a basis for S. chinensis being used as either a medicine or health food.…”
mentioning
confidence: 99%